Penguatan Kapasitas Tanggap Darurat Masyarakat Melalui Edukasi Kesehatan Stroke Akut Di Kecamatan Wanaraya - Ernawati .; Sri Purwanti Ariani; Indrayadi .; Yuhansya .; Nur Nadia (CV. ITTC INDONESIA, 2026)
Acute stroke is a medical emergency that can lead to permanent disability or death if not managed promptly and appropriately. In Wanaraya District, high population density, limited access to health care services, and low levels of health literacy contribute to suboptimal community preparedness in recognizing early signs of stroke and providing first aid. Despite strong social potential, such as the presence of community health volunteers and a culture of mutual cooperation, the community’s ability to identify stroke symptoms and respond rapidly remains limited. This activity aims to improve community knowledge and skills in recognizing the signs and symptoms of acute stroke and in providing timely, appropriate, and safe first aid through simulation-based emergency training. The program is expected to strengthen community preparedness and self-reliance in managing daily health emergencies, particularly acute stroke cases. In addition, this activity supports the achievement of Sustainable Development Goals (SDGs) Goal 3 on good health and well-being and contributes to strengthening the role of higher education institutions in community service activities.